2011
DOI: 10.1111/j.1745-4514.2011.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Oxidative Stress in Diethylnitrosamine-Induced Hepatocarcinogenesis: Chemopreventive Effect of Curcumin

Abstract: This study investigated the effect of curcumin against diethylnitrosamine (DEN)‐induced hepatocarcinogenesis. Rats were divided into three groups. The first group served as a control. The second group received DEN (orally, 20 mg/kg) five times a week for 8 weeks, followed by 10 mg/kg for another 7 weeks. The third group was supplemented with 2% curcumin diet simultaneously with DEN. The results showed normalization of serum level of total antioxidant capacity, γ‐glutamyl transferase and aminotransferase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…Because GST‐pi (π) and ‐mu (μ) are the most extensively studied proteins in the GST superfamily, this study investigated the levels of GST isozymes alpha and mu in the DEN‐induced HCC model. Although several studies have reported that DEN‐induced carcinogenic liver injury could increase or decrease the hepatic activities of GST, we found that liver GST activities increased in rats fed with NLE and DEN. This suggests that NLE treatment contributes to liver protection against DEN‐induced free radicals and subsequent hepatocellular damage (Figures C and A).…”
Section: Discussioncontrasting
confidence: 78%
“…Because GST‐pi (π) and ‐mu (μ) are the most extensively studied proteins in the GST superfamily, this study investigated the levels of GST isozymes alpha and mu in the DEN‐induced HCC model. Although several studies have reported that DEN‐induced carcinogenic liver injury could increase or decrease the hepatic activities of GST, we found that liver GST activities increased in rats fed with NLE and DEN. This suggests that NLE treatment contributes to liver protection against DEN‐induced free radicals and subsequent hepatocellular damage (Figures C and A).…”
Section: Discussioncontrasting
confidence: 78%
“…4). These findings converge with those observed in the studies of Seufi et al, (2009) and Darwish and El-Boghdady., (2011).Microscopic investigation for liver tissue sections of rat administered NDEA and treated with DOXO showed fine fibrosis with brown pigment in between the hepatocytes (Figures 5 and 6). These observations fit with those obtained by El-Sayyad et al, (2009).…”
Section: Histopathologysupporting
confidence: 92%
“…In group 3 , rats received DEN (20 mg/kg b.wt.) orally 5 times a week for 6 weeks 16 and left alive for 6 weeks; Group 4 rats were given DEN as in group 3 after that they were exposed to a single dose of gamma radiation 0.5 Gy (IR) and left alive for 6 weeks. In group 5 , rats were given DEN as in group 3 and after that, rats were supplemented with the GaNPs for 6 weeks till the end of the experiment.…”
Section: Methodsmentioning
confidence: 99%